Possible aerosol transmission of COVID-19 and special precautions in dentistry - Ge, Zi-yu; Yang, Lu-ming; Xia, Jia-jia; Fu, Xiao-hui; Zhang, Yan-zhen (Journal of Zhejiang University. B. Science, 2020)
Since its emergence in December 2019, corona virus disease 2019 (COVID-19) has impacted several countries, affecting more than 90 thousand patients and making it a global public threat. The routes of transmission are direct contact, and droplet and possible aerosol transmissions. Due to the unique nature of dentistry, most dental procedures generate significant amounts of droplets and aerosols, posing potential risks of infection transmission. Understanding the significance of aerosol transmission and its implications in dentistry can facilitate the identification and correction of negligence in daily dental practice. In addition to the standard precautions, some special precautions that should be implemented during an outbreak have been raised in this review.